Self-Evaluation and Warehouse Management on Employee Performance PT Zaindo Putra Logistics Banjarmasin - Nur Achmad Jabrial; Kamsariaty Kamsariaty; Mardiana Mardiana; Harmuzan Tazril (East Asian Journal of Multidisciplinary Research, 2023)
Performance assessment is included in human resources, comparative human resources are the key to the company's success. By conducting performance assessments on employees, employees will always try to do the maximum possible in every activity provided by the company or leaders and managers, and it will also be easy for them to carry out company activities in the field of increasing employee positions or seeing employee performance that is not optimal. The research method used is descriptive qualitative research. The conclusions in this research include assessing self-evaluation and performance of warehouse employees, which is the activity of managers or superiors to evaluate employee work performance behavior and determine subsequent policies. Performance appraisal is not a punishment but a form of leadership attention towards employees.Performance assessment is included in human resources, comparative human resources are the key to the company's success. By conducting performance assessments on employees, employees will always try to do the maximum possible in every activity provided by the company or leaders and managers, and it will also be easy for them to carry out company activities in the field of increasing employee positions or seeing employee performance that is not optimal. The research method used is descriptive qualitative research. The conclusions in this research include assessing self-evaluation and performance of warehouse employees, which is the activity of managers or superiors to evaluate employee work performance behavior and determine subsequent policies. Performance appraisal is not a punishment but a form of leadership attention towards employees.